(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the portrayal of hospitality in literature from socio-cultural and ethical perspectives, focusing on how traditional values are interpreted in the context of modern society. Using the prominent Uzbek author Tohir Malik’s novel Shaytanat as a case study, it analyzes a wedding scene to reveal how hospitality is expressed, how guests are received, and what hidden motives may lie behind such seemingly generous behavior. The article also compares this with other literary depictions of weddings, emphasizing the transformation of hospitality from a symbol of sincerity into a tool of influence and status. Ultimately, the study calls for preserving the authenticity of hospitality as a marker of human kindness rather than a performance of power or gain.